Public service broadcasting model in Indonesian transitional democracy - Masduki Masduki (Jurnal Kajian Komunikasi, 2022)
The emergence of the public service broadcasting (PSB) system in post-authoritarian countries in Asia, including Indonesia (after the 1998 political reform), is not in line with the aspiration of the democratic media system. Most public-oriented broadcasters were born as a hybrid of universal and ideal models of a democratic channel with local and transitional media systems. This article presents an analysis of various PSB models rooted in different countries. It examines the efforts made by Indonesian stakeholders to formulate an Indonesian style of PSB from 2002 until today. The qualitative method was used to review previous studies relating to PSB policies and governance throughout the world and official policies relating to the broadcast system in Indonesia. In-depth interviews were conducted with a former legislator who formulated Broadcast Law no. 32/2002, RRI and TVRI Supervisory Boards members, and media activists. The selected offices of the Radio of the Republic of Indonesia (RRI) and the Television of the Republic of Indonesia (TVRI) were also observed as the national PSB providers in Indonesia. This study found different pathways in PSB models (policy and governance) between developed democracies, such as the UK and Germany, and post-authoritarian countries, such as Indonesia. From a regulatory perspective, Indonesia’s PSB model is a mixture of the ideal form rooted in matured democracies with the old management of RRI/TVRI as ex-government channels. The hybrid PSB model has impeded RRI and TVRI’s transition to becoming actual public service broadcasters.